Efficacy Assessment of Different Botanicals Against Rice Weevil (Sitophilus Oryzae) in Stored Rice: Efficacy of Botanicals Against Rice Weevil in Stored Rice - Roy, Tapon Kumar (SAARC Journal of Agriculture, 2025)
Rice weevil (Sitophilus oryzae) is the major seed destroyer in stored grain, causing both quantitative and qualitative losses. Traditional approaches utilizing chemical insecticides including fumigants to address this problem present environmental risks and health concerns. Focusing on the scenario, a study was conducted at laboratory condition of entomology division, Bangladesh Rice Research Institute (BRRI) to assess the efficacy of different botanicals for the management of rice weevils in stored rice. Employing a Complete Randomized Design (CRD) with three replications, the experiment comprised four treatments alongside an untreated control, namely Neem (Azadirachta indica) oil, Mahogany (Swietenia macrophylla) seed kernel powder, Neem (A. indica) leaf powder, Biskatali plants (Polygonum hydropiper) powder and Control (untreated). The findings unveiled that the highest percent of insect mortality was found in neem oil (85%) was followed by biskatali plant powder (75%), neem leaf powder (61.67%), and mahogany seed kernel powder (60%), respectively. The lowest emergence of F1 progeny was recorded in neem oil-treated seeds compared to mahogany seed kernel, Neem leaf powder, biskatali, and untreated control, indicating the efficacy in managing the reproductive capacities of rice weevils. Additionally, neem oil also exhibited the least weight (%) loss of grain compared to other treatments. Regarding seed germination, biskatali plant powder showed the highest germination rate (94%), followed by neem leaf powder (90%), mahogany seed kernel powder (89.67%), neem oil (88%), and control (80.67%), respectively. The research findings indicated that the neem oil and biskatali plant powder have the greatest potential to minimize the current use of synthetic insecticides for rice weevil management in stored rice. SAARC J. Agric., 22(2): 197-207 (2024)